Sectoral transformation, turbulence, and labor market dynamics in Germany - Ronald Bachmann; Michael C. Burda (Institute for the Study of Labor (IZA), 2008)
This paper analyzes the interaction between structural change and labor market dynamics in West Germany, during a period in which industrial employment declined by more than 30% and service sector employment more than doubled. Using transition data on individual workers, we document a marked increase in structural change and turbulence, in particular since 1990. Net employment changes resulted partly from an increase in gross flows, but also from an increase in the net transition yield at any given gross worker turnover. In growing sectors, net structural change was driven by accessions from nonparticipation rather than unemployment; contracting sectors reduced their net employment primarily via lower accessions from nonparticipation. While gross turnover is cyclically sensitive and strongly procyclical, net reallocation is countercyclical, meaning that recessions are associated with increased intensity of sectoral reallocation. Beyond this cyclical component, German reunification and Eastern enlargement appear to have contributed significantly to this accelerated pace of structural change.
Keywords: J63; 330; Gross worker flows; sectoral and occupational mobility; turbulence; Strukturwandel; Strukturelle Arbeitslosigkeit; Arbeitsmobilität; Deutschland